Pengaruh Model Inquiry-Based Learning Berbasis Etnosains Rumah Lengge terhadap Kemampuan Berpikir Logis Siswa Sekolah Dasar - Asriyadin Asriyadin; Muhammad Fuadi; M. Ibnusaputra; Khairil Anwar (STKIP Taman Siswa Bima, 2025)
This study aims to analyze the effect of the Inquiry-Based Learning (IBL) model integrated with Rumah Lengge ethnoscience on elementary school students’ logical thinking skills. The background of this research is rooted in the low level of students’ logical reasoning abilities, which are still dominated by conventional teaching methods that lack contextual relevance and fail to stimulate scientific reasoning. This quantitative study employed a one-group pretest-posttest design involving one experimental class of 25 fifth-grade students in Wawo District, Bima Regency. The research instrument consisted of a logical thinking skills test based on Ennis' (1996) indicators, comprising 10 multiple-choice items with reasoning. Data were analyzed using a paired sample t-test to examine significant differences between pretest and posttest scores. The results indicated a notable increase in the average score from 61.7 to 71.6, with a statistically significant difference (t = -28.4; p < 0.001). The normality test on the residuals confirmed that the data met the requirements for parametric analysis. These findings demonstrate that the IBL model based on Rumah Lengge ethnoscience is effective in enhancing students’ logical thinking skills by integrating scientific inquiry processes with relevant and meaningful local cultural contexts. The implication of this study suggests that locally contextualized inquiry-based approaches can serve as a strategic alternative to improve the quality of science education in elementary schools.